Assessment of factors predicting the nutritional status of geriatric people in Tabuk, Saudi Arabia - Samar Lafi Aljohani (Journal of Family Medicine and Primary Care)
Background: On a global level, geriatric malnutrition is a substantial problem as it has many adverse health outcomes including increased morbidity and death rates, in addition to poor health-related quality of life. This study aims to assess the nutritional status of patients attending geriatric clinics at hospitals. Material and Methods: An observational cross-sectional study was conducted in Tabuk city, northern Saudi Arabia, among geriatric patients aged over 60 years who attended geriatric clinics throughout the study period (December, 2022 to February, 2023). A validated self-administered questionnaire was used in data collection. It includes demographic, habitual, and medical characteristics of the participants, anthropometric data (weight and height), and the validated short form of Mini Nutritional Assessment tool to assess their nutritional status. Results: The study included 307 geriatric patients out of targeted 362 (response rate = 84.8%). The age of almost half of them (49.2%) ranged between 60 and 69 years, and males constituted 56.4% of them. Overall, 17.3% of the participants were malnourished, whereas 41.4% were at risk of malnutrition. Results of multivariate logistic regression analysis revealed that compared to married participants, widowed participants were at higher significant risk for malnutrition [adjusted odds ratio (aOR): 2.59, 95% confidence interval (CI): 1.01–6.85, P = 0.049]. Compared with participants who were living alone, those living with their spouse were at 86% lower risk for malnutrition (aOR: 0.14, 95% CI: 0.03–0.62, P = 0.010). Overweight and obese subjects were at significant lower risk for malnutrition as compared to underweight subjects (aOR: 0.04, 95% CI: 0.01–0.44, P = 0.008 and aOR: 0.05, 95% CI: 0.01–0.54, P = 0.013, respectively). Participants who never practiced exercise or practiced it irregularly were at higher risk for malnutrition as opposed to those who practice physical activity regularly (aOR: 3.45, 95% CI: 1.42–8.38, P = 0.006 and aOR: 3.60, 95% CI: 1.48–8.77, P = 0.005, respectively). Patients with more than three chronic disease/heath problems were at 4-fold risk for developing malnutrition as compared to those without history of chronic diseases/health problems (aOR: 4.0, 95% CI: 1.31–12.17, P = 0.015). Conclusion: Malnutrition is a public health problem affecting a considerable proportion of geriatric people in Tabuk, southern Saudi Arabia, with some modifiable risk factors associated with malnutrition.